A study of regional cerebral blood flow and cognitive performance in Alzheimer's disease. - O'Brien, J T (1992)
Thirty five patients with dementia of the Alzheimer type (DAT) and 35 controls matched for age, sex and handedness were investigated using single photon emission computer tomography (SPECT) with 99m technetium HMPAO. Regional cerebral blood flow (rCBF) was assessed semi-quantitatively in 18 cortical and 4 subcortical areas by normalising mean information density in each region to cerebellar mean information density. Analysis revealed significantly reduced rCBF to temporal, parietal, frontal and left occipital cortex in the patients whilst blood flow to subcortical areas showed no differences between the 2 groups. In addition, significant left-sided cortical hypoperfusion was seen in the DAT group but not in controls. When patients were sub-divided on the basis of disease severity, those with mild disease showed temporal, parietal and left frontal changes with more severely affected patients also showing right frontal and left occipital involvement. rCBF patterns did not distinguish between presenile and senile onset cases once duration and severity of illness were controlled. Eight cortical areas were also rated visually for perfusion deficits on a simple 4 point scale. Perfusion deficits were detected in 34 of 35 patients but in only 4 of 35 controls. In the DAT group significant correlations were found between many of the neuropsychological tests used and rCBF. Memory correlated with left temporal activity, praxis, perception, object assembly and block design with right parietal activity and language with activity throughout the left hemisphere. Significant correlations were also seen between subcortical and cortical blood flow, possibly explaining the correlations observed between many of the neuropsychological tests and thalamic blood flow.